Peak Oil Theory in Canada’s Globe and Mail: A Case Study of the Construction of Ignorance - Kranakis, Eda (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2014)
Scientific knowledge is essential to understand problems confronting society, and the mass media have become the main source of this knowledge for most people. However, the mass media filter scientific information, leading sometimes to what has been termed “the construction of ignorance.” This article offers a case study of this process. It explains how Canada’s leading newspaper, the Globe and Mail, has depicted oil depletion theory (or “peak oil” theory). By contrasting the history of oil depletion theory with its representation in the Globe and Mail since the turn of the millennium, the article reveals the contours of this constructed ignorance. Comparison with coverage of meteorological and climate change science further refines the analysis. Finally, the article investigates the underlying causes for the Globe and Mail’s treatment of peak oil theory and how it relates to the Canadian context.